Anatoly Mykhaylovych Nenko - Ukrainian association of orthopaedists-traumatologists, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 75th birthday of the Head of Eupatoria Central Children’s Clinical Sanatorium of the Ministry of Defence ofUkraine, winner of the State Prize of Ukraine, Honoured Doctor of Ukraine, Candidate of Medical Science, Colonel of Medical Service A.M. Nenko.